Keystone virus: a mosquito-borne arbovirus - Abdullah A. Alomar; Lawrence E. Reeves; Barry W. Alto (EDIS)
Keystone virus (KEYV) is an emerging negative-sense single-stranded RNA arthropod-borne virus (arbovirus) that can be transmitted to humans by the bite of an infected mosquito vector. This publication provides an overview of the KEYV distribution, potential vectors, transmission cycle, symptoms, diagnosis, and prevention.